Perdagangan Banten- Manila, 1663-1682 - Mufti Ali (Jurnal Masyarakat dan Budaya, 2021)
This research paper aims to explore Banten-Manila trade network by answering three following research questions: (1) how did the Banten sultanate establish its trade network to Manila; (2) how did Banten maintain its commercial connection to Manila?; (3) how was the banten-manila trade cut by the Dutch? The method which is applied in this research is historical method, which comprises four following steps: heuristic, critic, interperation and historiography. Historical sources which are made use of in this research are primary sources, mainly dagh register (VOC archives) and diaries of Catholic missionaries in Philipine. My study of primary sources consistently shows that Bantenese ships transported two important commodities; cloth and iron to Manila and brought home Spanish coins. Besides cloth and iron, Bantenese ships also transported pepper and other commodities to Manila; these included rice, Japanese copper, and sappan wood (caesalpina sappan). The most prosperous period in the history of the Sultante of Banten was during its trade relations with Manila, from 1663-1682. The trade relations had resulted in the Sultanate of Banten to send ships to many harbours; from Siam, to China, Gujarat, Pegu, Coromandel, Madraspatnam, Surat, Macao, Vietnam, Persia, Mocha and London.